MekHanTropia: autoconhecimento e (re)existência em um universo transmidiático, experimental, colaborativo e autoral - Felipe, Frederico Carvalho (2023)
Hypercompetitiveness, hyperinformation, hyperproductivity and hyperconsumption – 24/7 (hours/days) – generate new anxieties in individuals who are increasingly standardized according to the market. Thus, I think poetically about this thesis-creation about how we currently deal with telematic flows and subjectivities today, placing myself through creative processes as an object of artistic experimentation to build a transmedia dream universe that I call 'MekHanTropia'. Through poetic artistic creations using different languages, tools and platforms, I create a cosmology that represents some of my subjective experiences in times of high human dispersion due to the pandemic. I envision ways to (re)exist through countercultural artistic resistance, questioning psychopolitical standards and Manichaean binaries dictated by the market and reflect, in this process, on collaborative art, experimental and conceptual art, poetic resignifications, polysemic relationships between art and technology, dreamlike narratives, intertextualities and other practices that aim at selfknowledge and confronting institutionalized mekHanTropic psychobinary obscurantism through resignification and artistic materialization.